Transcriptional Coactivator BOB1 (OBF1, OCA-B) Modulates the Specificity of DNA Recognition by the POU-Domain Factors OCT1 and OCT2 in a Monomeric Configuration - Igor B. Nazarov; Danil S. Zilov; Mikhail N. Gordeev; Evgenii V. Potapenko; Nataliya Yeremenko; Alexey N. Tomilin (Biomolecules, 2024)
BOB1, a mammalian lymphocyte-specific transcriptional coactivator of the transcription factors OCT1 and OCT2 (OCT1/2), plays important roles in normal immune responses, autoimmunity, and hematologic malignancies. The issue of a DNA sequence preference change imposed by BOB1 was raised more than two decades ago but remains unresolved. In this paper, using the EMSA–SELEX–Seq approach, we have reassessed the intrinsic ability of BOB1 to modulate the specificity of DNA recognition by OCT1 and OCT2. Our results have reaffirmed previous conclusions regarding BOB1 selectivity towards the dimer configuration of OCT1/2. However, they suggest that the monomeric configuration of these factors, assembled on the classical octamer ATGCAAAT and related motifs, are the primary targets of BOB1. Our data further specify the DNA sequence preference imposed by BOB1 and predict the probability of ternary complex formation. These results provide an additional insight into the action of BOB1—an essential immune regulator and a promising molecular target for the treatment of autoimmune diseases and hematologic malignancies.